Patient's Awareness Regarding Prevention of Recurrent Urinary Tract Stones in Surgical Teaching Hospital in Sulaimani City, Iraq - Ismael, Niyan Hakim (Sulaimani Journal for Pure and Applied Sciences, 2021)
Urinary tract stone is the most common recurrent disorder of the urinary tract that encompasses all the process of stone formation in the urinary system (kidney, ureter, bladder, and urethra). Patient’s awareness could prevent the disease and its consequences. The aim of this study is to assess the patient’s awareness regarding prevention of recurrent urinary tract stones. A quantitative, descriptive study was carried out in Surgical Teaching Hospital in Sulaimani City, from June to September 2020. A total number of, 50 patients who had urinary stones were recruited into the study, and required data were collected through direct interviews. The questionnaire was used to collect data on the patients’ Sociodemographic and awareness of the urinary tract stones. Questions about awareness of urinary stones were related to fluid and beverage intake, past medical history and risk factors, movement and physical activity, and dietary intake. The collected data were analyzed through Statistical Package for the Social Sciences (version 22.0). The results of the present study showed that most of the patients’ aged30 to 60 years, were males (58%), and had primary level of education (38%). Patient’s awareness regarding “fluid and beverage intake, past medical history and risk factor, physical activity and dietary intake” was considerably at a moderate level. There was no significant relationship between the patients’ socio-demographics and their awareness of the urinary tract stones It was concluded that the patients were not sufficiently aware of urinary tract stone prevention. Patient’s socio-demographic variables did not determine the patients’ awareness of stone prevention.
Keywords: Awareness; Recurrent urinary tract stones; Socio-demographic characteristics